Fortification of Dry Cakes with Fish Flour to Enhance Nutritional Value: A Review - Junianto Junianto; Diyah Ayu Anggreini (Nekton, 2025)
Fishmeal is a rich source of animal protein and essential nutrients, offering significant potential for food fortification, particularly in cookies and pastries, which are typically low in protein. This article presents a literature review of various studies evaluating the addition of fishmeal derived from local fish species such as biang, anchovy, mackerel, swanggi, and roa in the production of baked goods. The findings show that incorporating fishmeal at concentrations between 10–20% significantly increases products' protein content—for example, Swanggi fish biscuits reaching 19.91% protein and roa fish sticks reaching 15.44%. Several products also showed increased mineral content, such as calcium up to 820.63 mg/100 g. The sensory qualities remained acceptable to consumers, provided the addition levels were not excessive. A primary challenge remains the distinct fishy odor, which can affect consumer acceptance but can be mitigated through appropriate processing techniques. This review concludes that cookie fishmeal fortification is an innovative strategy for improving nutritional quality and utilizing local fishery by-products.